أثر مستوى الضوضاء على مستوى العلاقات الاجتماعية - شنة, محمد رضا; إسعادي, فارس (جامعة الوادي University of Eloued, 2018)
تهدف الدراسة الى معرفة أثر مستوى الضوضاء على مستوى العلاقات الاجتماعية بالمنظمة الصناعية، حيث تم الاعتماد على المنهج الوصفي بطريقة المقارنة، والاستبيان لجمع المعلومات من الميدان، تم توزيعه على عينة عرضية قوامها 180 فرد ولغرض معالجة المعطيات المستمدة من الميدان تم الاعتماد على اختبار ت لدلالة الفروق حيث تم التوصل الى النتائج التالية: - توجد فروق ذات دلالة إحصائية عند المستويين 0.01 و0.05 في مستوى العلاقات الاجتماعية بين العمال الذين يعملون في بيئة عمل ذات مستوى ضوضاء مرتفع وبين العمال الذين يعملون في بيئة عمل عادية.ABSTRACT:The study aims at identifying the effect of noise level at the level of social relations in the industrial organization, where the descriptive approach was based on comparison method The questionnaire for collecting information from the field was distributed to a cross-sectional sample of (180) individuals. For the purpose of processing data from the field, the results were based on the following results: There are statistically significant differences at levels of(0.01) and (0.05) in the level of social relations between workers working in a high noise level work environment and those working in a normal work environment.
لدى العاملين في المؤسسات الصناعية
مقال
Keywords: الضوضاء ،العلاقات الاجتماعية; noise; social relations